2016
DOI: 10.1097/j.pain.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Symptom profiles in the painDETECT Questionnaire in patients with peripheral neuropathic pain stratified according to sensory loss in quantitative sensory testing

Abstract: The painDETECT Questionnaire (PDQ) is commonly used as a screening tool to discriminate between neuropathic pain (NP) and nociceptive pain, based on the self-report of symptoms, including pain qualities, numbness, and pain to touch, cold, or heat. However, there are minimal data about whether the PDQ is differentially sensitive to different sensory phenotypes in NP. The aim of the study was to analyze whether the overall PDQ score or its items reflect phenotypes of sensory loss in NP as determined by quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
1
26
1
2
Order By: Relevance
“…Contrary to published literature, this study did not find associations between pain sensitivity and age, race, cancer stage, anxiety, fatigue, sleep-wake disturbance, cognitive difficulty, childhood trauma experience, or widespread pain (El Tumi, Johnson, Dantas, Maynard, & Tashani, 2017;Tesarz, Eich, Treede, & Gerhardt, 2016;Vaegter & Graven-Nielsen, 2016). The evidence of associations between pain sensitivity and age, socioeconomic factors, and neuropathic pain presence and severity has been inconsistent and is inconclusive (El Tumi et al, 2017;Martinez et al, 2015;Vaegter & Graven-Nielsen, 2016;Vollert et al, 2016). Although evidence suggests that many symptoms share common central nervous system-mediated pathways and contribute to processes that increase pain sensitivity (Burnstock, 2015;Campbell et al, 2015;Clauw & Chrousos, 1997;Goesling, Clauw, & Hassett, 2013), the current study may have been unable to detect symptom associations found in prior studies because of the small sample size or low symptom severities in the presurgical sample.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Contrary to published literature, this study did not find associations between pain sensitivity and age, race, cancer stage, anxiety, fatigue, sleep-wake disturbance, cognitive difficulty, childhood trauma experience, or widespread pain (El Tumi, Johnson, Dantas, Maynard, & Tashani, 2017;Tesarz, Eich, Treede, & Gerhardt, 2016;Vaegter & Graven-Nielsen, 2016). The evidence of associations between pain sensitivity and age, socioeconomic factors, and neuropathic pain presence and severity has been inconsistent and is inconclusive (El Tumi et al, 2017;Martinez et al, 2015;Vaegter & Graven-Nielsen, 2016;Vollert et al, 2016). Although evidence suggests that many symptoms share common central nervous system-mediated pathways and contribute to processes that increase pain sensitivity (Burnstock, 2015;Campbell et al, 2015;Clauw & Chrousos, 1997;Goesling, Clauw, & Hassett, 2013), the current study may have been unable to detect symptom associations found in prior studies because of the small sample size or low symptom severities in the presurgical sample.…”
Section: Discussioncontrasting
confidence: 97%
“…Some studies in other chronic pain populations support the individualization of pain treatment based on QST indicators of abnormal pain-processing mechanisms (Rabey, Slater, O'Sullivan, Beales, & Smith, 2015;Vollert et al, 2016). Other literature suggests tailoring interventions based on genotype, self-reported symptom clusters, comorbidities, and pain severity and catastrophizing (Ahmedzai, 2013;Cherkin et al, 2016;Hill et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Currently there is a growing interest in characterizing the somatosensory profile of patients with chronic pain using both validated questionnaires and quantitative sensory testing (QST) . This may not only allow us to subgroup patients based on underlying mechanisms but also helps us to identify suitable targets for treatment and perhaps might help us differentiate responders from non‐responders .…”
Section: Introductionmentioning
confidence: 99%
“…The painDETECT questionnaire has been developed as a neuropathic screening tool for assessing neuropathic components in chronic musculoskeletal pain, such as chronic LBP (Freynhagen et al, 2006) and OA (Hochman et al, 2013), but it is not specifically useful for neuropathic pain conditions with sensory loss (Vollert et al, 2016). More recently another mechanism-based classification questionnaire has been developed for LBP to identify symptoms and signs associated with a clinical classification of CS in patients with low back (AE leg) pain (Smart et al, 2012).…”
Section: Clinical Assessment Of Central Sensitisationmentioning
confidence: 99%